2016
DOI: 10.1002/erv.2473
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction in Bulimia Nervosa: Clinical Correlates and Association with Response to a Brief Psychoeducational Intervention

Abstract: Food addiction appears to be prevalent in BN although FA severity can improve following a short-term intervention. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 30 publications
4
42
1
2
Order By: Relevance
“…Only one study was identified with a high proportion of males (92%, in a veteran study) (62) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study was identified with a high proportion of males (92%, in a veteran study) (62) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…The most common population group studied were those individuals seeking a weight-loss treatment (n = 11 studies) (18,24,35,(39)(40)(41)44,51,66,78,79) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . The studies carried out in disordered eating groups all included bulimia nervosa (BN) and BED, with only two studies including additional eating 109 (0.99), Eating concern 3.14 (0.95) versus 0.57 (0.66), Shape concern 4.54 (0.96) versus 1.98 (1.32), Weight concern 3.99 (1. with negative affect and emotional dysregulation, and negatively correlated with self-esteem (P = 0.01).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The YFAS is a self‐report measure that adapts the DSM criteria for substance‐use disorders to evaluate addictive‐like consumption of foods high in fat and/or refined carbohydrates (Gearhardt, Corbin, & Brownell, , ). The YFAS has been associated with clinically relevant features, such as frequency of binge eating episodes, weight cycling, obesity, and short‐term abstinence from binging‐purging in persons with bulimia nervosa following intervention (Davis et al, ; Gearhardt, Boswell, & White, ; Granero et al, ; Hilker et al, ; Schulte & Gearhardt, ). However, many previous studies of food addiction have consisted of small samples or samples with limited generalizability to the national population (e.g., clinical samples, undergraduates, overrepresentation of females and White individuals).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to therapy response , based on the literature, it has been observed that higher FA, according to YFAS scoring, has been associated with poorer treatment outcome in the case of eating disorders, specifically in Bulimia nervosa (Hilker et al, ), and also in Bariatric Surgery obese patients, where those with FA experienced more difficulties reducing weight prior to the BS (Guerrero Pérez, et al, ) and post‐operatively (Miller‐Matero et al, ).…”
mentioning
confidence: 99%